DEVELOPMENT OF KINDERGARTEN LEARNING MODULES BASED ON BLENDED LEARNING IN THE DIGITAL ERA - Riyan Maulana; Fahmi Hanifa; Saddam (Jurnal Penelitian Progresif, 2026)
Kindergarten is a golden age for maximizing intellectual potential. However, the development of students' basic skills has not yet reached the expected target. This research was conducted to address this issue by developing a blended learning-based module. Blended learning was chosen because it is tailored to learning during the pandemic. The module development steps followed the ADDIE development model. The module was piloted with content experts, instructional design experts, small groups, and field trials. The validation results of the content expert test obtained a feasibility score of 95% and the instructional design expert test a 90%. The average feasibility score in the small group test was 91% and the field test a 95%. This blended learning -based module makes a significant contribution to learning during the pandemic because it provides a solution to learning challenges. The use of the module can increase student activity and motivation, even for physical activities. Blended learning is also an effective means of introducing students to the use of technology.